BUDAYA ORGANISASI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI RIAU - Fara Merian Sari (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
Organizational Culture is a shared value system in an organization that is a reference for how employees carry out activities to achieve the goals or goals of the organization. This is stated as the vision, mission and goals of the organization. Organizational culture is developed from a collection of norms, values, beliefs, hopes, assumptions, and philosophies of the people in it. The purpose of this research is to find out and analyze the Organizational Culture of the One-Stop Integrated Investment and Services Office of Riau Province and to analyze the obstacles in the Organizational Culture of the Department of Investment and One-Stop Integrated Services of the Riau Province. In this study the authors use the concept of theory according to Jerald Greenberg and Robert A. Baron (2010: 36) suggesting that there are seven elements that show the characteristics of organizational culture, among others, innovation, stability, orientation to people, orientation to results, being calm , attention to details, orientation to collaboration